PEMBANGUNAN APLIKASI EXPLORE WISATA DI KOTA LANGSA - Hibabullah, Aufa; Pranada, Rama Handy; Adipraja, Farhan Munawar; Nugroho, Sigit Aryobimo; Arafad, Yusmardoli (Majalah Ilmiah UNIKOM, 2019)
Tourism is a trip carried out for recreation or leisure. Langsa City is one of the cities in Aceh, the total area of ​​the city of Langsa is 262.4 km². There are still many people in and out of the city of Langsa who do not know of existing tourist destinations and transportation to go to the city of Langsa, so tourists lack information on transportation and tourist destinations in the city of Langsa. From this research, an application will be made to explore android-based tours that can provide tourist information and estimate costs. The method of research carried out in the construction of applications explore tours and compilers of reports is the method of data collection, analysis and design, implementation, testing, and drawing conclusions. Travel explore application is built for the android platform and uses ionic as a framework. Based on the testing that has been carried out the application built has been able to provide information about tourist destinations in the city of Langsa and can estimate the costs to be incurred by tourists. Keywords: Tourism, Langsa City, Explore Tourism, Android.